Pengaruh Tayangan Debat Calon Presiden di Media Penyiaran Multi Platform terhadap Partisipasi Politik pada Pemilu 2024 : Survei pada Mahasiswa Fisip UMJ Angkatan 2020 - Siti Mutyasari; Mulkan Habibi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Political participation is an important aspect in a democratic state structure, as well as a characteristic feature of political modernization. Political participation influences the legitimacy of society regarding the running of a government. One way of implementing political participation is through General Elections (Pemilu). The aim of this research is to determine the influence of presidential candidate debate broadcasts on multi-platform broadcast media on the political participation of FISIP UMJ student class of 2020. This research has an independent variable, namely presidential candidate debate broadcasts with the dimensions of frequency, attention and duration, and has a dependent variable, namely providing voting rights in elections, lobbying with officials, becoming a member of a political party. This research method uses a survey method by distributing questionnaires online to respondents via Google Form which aims to collect data from a sample of 2020 FISIP UMJ students who actively watch presidential candidate debates and know about political participation, with a total of 66 respondents selected. The data collection tool uses a questionnaire using a Likert Scale. The results of this research show that the presidential debate broadcast has an influence on political participation, which has a value of 0.736 or 73.6%, which means that the presidential debate broadcast influences political participation by 73.6% and the rest is influenced by other factors.